Visitors' preferences for museum interpretation - Sedmak, Gorazd (Academica turistica, 2017)
A number of heritage studies have revealed that interpretation is an essential com- ponent of the visitor experience. However, visitors differ in their interests in inter- pretation. Preferences for interpretation, which are often neglected in the literature, are essential for the marketing and management of heritage organisations. This pa- per deals with visitors% preferences for museum interpretation to determine what the preferred types of interpretation of museums exhibits are and what the differ- ences between the segments of visitors in this regard are. The research focuses on seven Adriatic heritage museums that took part in the cross-border project on the strengthening of cultural tourism through market-oriented initiatives. The survey set out to obtain information on visitor profiles and their preferences for museum interpretation. By isolating and analysing interpretation variables and visitor vari- ables associated with visitor interpretation preferences, a framework was developed that enable the initiatives in museum interpretation for target market segments.
Keywords: kulturni turizem; motivacija; motivation; muzeji